The relationship between social care receipt and home death in Scotland during the first year of the Covid-19 pandemic - Savinc, Jan; Atherton, Iain (International Journal of Population Data Science, 2025)
Objectives To assess the completeness of social care data regarding people in the final year of life in the five years leading up to and first year of the pandemic in Scotland, and to ascertain the extent to which provision responded to increased home deaths. Methods A comparative retrospective cohort study of people approaching the end of life using Scottish death registrations March 2015-March 2021 with linked hospital admissions (SMR01) and social care data (SOURCE). The completeness of data across Scotland will be assessed using descriptive statistics. Proportions of social care and unpaid care receipt will be compared over time to assess the extent to which formal care was able to respond to increased deaths at home and whether the increase can be explained by unpaid care provision. Results In total, 21,705 people died at home in the first year of the pandemic, a 35.6% increase over the 12 months prior. Proportions of people receiving care social care in the final year of life will be compared over time and between geographical areas. Statistical models will be developed to test the association of care receipt with need as represented by the Elixhauser Comorbidity Index and living arrangements, and the association of home death with social care and unpaid care receipt, as well as how those associations changed with the Covid-19 pandemic. Conclusion Social care data has been underutilised in data linkage studies. Findings of this study have implications both for use of social care data and for understanding increased home deaths, a shift that has continued since the onset of the Covid-19 pandemic in Scotland.